Reflections Toward an Enactive Psychoanalysis. Issue 4 (2nd October 2017) - Pulido, Ricardo
ABSTRACT: The present work examines the meaning of embodied mind—a key notion in the thinking of biologist and epistemologist Francisco Varela—as an answer for the paradoxes and blind spots originated by the representationist approaches that underlie theories of the mind of most psychological and philosophical schools, including Freudian psychoanalysis. The understanding of this notion implies a radical review of our beliefs regarding the substantial reality of the self, the world, and the relationship between them. For this reason Varela suggests that only a nondiscursive nonanalytic praxis can allow the subject to carry on the observation, inquiry, and acceptance of the experience of himself or herself, the other, and the world as empty and groundless.. Two preliminary reflections are discussed in the paper: (a) the possibility of developing an enactive psychoanalysis, that is, a psychoanalysis that understands the experience of the constitutive frailty of the self as a potentially liberating one rather than as a flaw in the structuring of personality and its defense mechanisms, and (b) how to introduce the method of Mindfulness in the psychotherapeutic setting without interfering with the psychoanalytic listening or the patient and analyst's relational work.